WATER IN THE BULGARIAN WORLD PICTURE (a case study of the folk songs of the Bulgarians in Ukraine) - MALASH, Oleksandra (Linguistic and Conceptual Worldviews, 2022)
The paper provides a study of the symbolism of water in the Bulgarian linguistic culture. The author analyzes texts of the folk songs recorded by several Ukrainian and Bulgarian scholars from the descendants of the Bulgarian migrants in the last half of the 18th - 19th c., which are currently living in the regions of Odessa, Zaporizhzhia, Mykolaiv, and in the Autonomous Republic of the Crimea. The role of the vocabulary around the hydrosphere in the Bulgarian linguistic world image is researched.It is outlined that water is a universal symbol of the human life. Water is thought as a primary substance that has created the Earth and the live nature. It is used in different liminal rituals as something able to purify, to heal, to charge with the live power and to bless people. And this belief in the sacral properties of water are displayed in the Bulgarian folk songs.The author investigates the linguocultureme "water" and its implementations in "reservoir", "well", "spring", "rain", "Danube", "sea" in the folk songs of the Bulgarians in Ukraine. It is established that "water" is a symbol of a border that must be overstepped. "Well" symbolizes the living space of a human, container of the unique sacral water that sacralizes the marriage and love. However, sometimes the well designates the adultery and lewdness. "Spring" is equal to the immortality given to a hero as a thank for the completed mission of the life. "Danube" is a mythic path between the known and unknown world, like "sea" it is a symbol of the separation with the home, and it is particularly true for the Bulgarian migrants whose ancestors had left the motherland. "Rain" represents the reciprocity between the human and the supreme forces.The analyzes of these implementation of the linguocultureme "water" shows the special role of the water in the Bulgarian linguistic world image.
Keywords: linguistic culturology, linguo-folklore studies, linguocultureme, Bulgarian language, Bulgarians in Ukraine, hydro vocabulary